The sustainability of Bamboo in the Philippines the level of awareness and utilization of Bamboo among selected design professionals and design students - Guinhawa, Joanna Katrina V.; Brasileno, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT The purpose of this study was to determine whether the level of awareness and utilization of bamboo among design professionals and design students impacts its sustainability in the Philippines. This quantitative study employed secondary data analysis, observation, interview, survey questionnaires, and documentation to obtain data needed for the study. A purposive sampling method was used for this study, the respondents were selected for their knowledge and experience on the utilization and sustainability of bamboo. Arch. Francisco Mañosa and Arch. Rosario Encarnacion ? Tan were interviewed as a panel of experts for this study. Both architects are pioneers in applying the principles of traditional Filipino architecture to contemporary design through the use of bamboo. A survey was conducted on design professionals consisting of 30 interior designers, 50 architects, and 6 furniture designers. A total of 90 interior design students and 90 architecture students were also included in the survey. Results showed that all respondents were aware of bamboo and its properties to a great extent. More than 65.56% of the respondents utilize bamboo now, and more than 83.3% of the respondents would utilize bamboo if there is a need to. Based on the findings of the study, Arch. Encarnacion ? Tan stated that there is less than 100,000 hectares of bamboo forests left in the Philippines. Currently, there is not enough to sustain the demand in the design industry today, given the rate of which bamboo is utilized and consumed. Therefore, in order to maintain the sustainability of bamboo in the country, measures to propagate and regulate bamboo forests is essential.
Thesis (B.S. Interior Design)--University oif the Philippines Diliman.
Keywords: Bamboo -- Philippines; Bamboo in interior decoration -- Philippines